Examining the influence of childhood trauma and epigenetic variation in brain-derived neurotrophic factor on anxiety sensitivity - Chifamba, Leah; Martin, Lindi; Seedat, Soraya; Hemmings, Sian; Womersley, Jacqueline (Stellenbosch : Stellenbosch University, 2022)
Thesis (MEng)--Stellenbosch University, 2022.